Angiotensin-converting enzyme gene: application possibilities in medicine and sports cardiology (literature review) - S. M. Malakhova (Zaporožskij Medicinskij Žurnal)
Aim. Formation of modern ideas about the effect of angiotensin-converting enzyme polymorphism on the functioning of various body systems including in athletes.